Cyclin D1 ( CCND1) A870G gene polymorphism modulates smoking-induced lung cancer risk and response to platinum-based chemotherapy in non-small cell lung cancer (NSCLC) patients - Gautschi, Oliver; Hugli, Barbara; Ziegler, Annemarie; Bigosch, Colette; Bowers, Naomi L.; Ratschiller, Daniel; Jermann, Monika; Stahel, Rolf A.; Heighway, Jim; Betticher, Daniel C. (Lung cancer (Amsterdam, Netherlands), 2006)
The cyclin D1 ( CCND1) A870G gene polymorphism is linked to the outcome in patients with resectable non-small cell lung cancer (NSCLC). Here, we investigated the impact of this polymorphism on smoking-induced cancer risk and clinical outcome in patients with NSCLC stages I–IV. CCND1 A870G genotype was determined by polymerase chain reaction (PCR) and restriction fragment length polymorphism analysis (RFLP) of DNA extracted from blood. The study included 244 NSCLC patients and 187 healthy control subjects. Patient characteristics were: 70% male, 77% smokers, 43% adenocarcinoma, and 27% squamous cell carcinoma. Eighty-one percent of the patients had stages III–IV disease. Median age at diagnosis was 60 years and median survival was 13 months. Genotype frequencies of patients and controls both conformed to the Hardy Weinberg equilibrium. The GG genotype significantly correlated with a history of heavy smoking (≥40 py, P = 0.02), and patients with this genotype had a significantly higher cigarette consumption than patients with AA/AG genotypes ( P = 0.007). The GG genotype also significantly correlated with tumor response or stabilization after a platinum-based first-line chemotherapy ( P = 0.04). Survival analysis revealed no significant differences among the genotypes. Evidence was obtained that the CCND1 A870G gene polymorphism modulates smoking-induced lung cancer risk. Further studies are required to explore the underlying molecular mechanisms and to test the value of this gene polymorphism as a predictor for platinum-sensitivity in NSCLC patients.